Effect of umbilical cord matrix stem cells on Parkinson’s disease model rats - Medicetty, Satish (Kansas State University, 2005)
Umbilical cord matrix or Wharton’s Jelly is a mucous connective tissue ensheathing the cord blood vessels and contains mesenchymal-like stem cells. Previously, we have shown that pig umbilical cord matrix stem (pUCMS) cells transplanted into normal rat brain were recovered up to 6 weeks post-transplantation, where a sub-population of pUCMS cells exhibited neuronal morphology and expressed a variety of neuronal markers. Here, approximately 150 pUCMS cells were transplanted into non-immunesuppressed rats that previously received a brain lesion by neurotoxin, 6-hydroxydopamine (6-OHDA), which specifically affects midbrain dopaminergic neurons, leading to pathologic findings similar to that of Parkinson’s disease (PD). The pUCMS cells proliferated up to 8 weeks post-transplantation and there was a significant increase in the percentage and number of pUCMS cells expressing tyrosine hydroxylase (TH), which is a marker for dopaminergic cells. We conclude that 1. Xenotransplants of pig UCMS cells are not rejected by rats at least up to 8 weeks after transplantation and 2. The pig UCMS cells proliferate and differentiate after transplantation into PD model rats. The surface antigen and gene expression profile of human umbilical cord matrix stem (hUCMS) cells resemble that of mesenchymal stem cells. Apomorphine-induced rotatory behavior was used to analyze the motor deficits of the PD model rats. In different experiments 1000, 2500 and 25000 hUCMS cells were transplanted into the brain of non-immunesuppressed PD model rats. There was a dose-dependent decrease in apomorphine-induced rotations; the maximum benefit was found in the rats that received 1000 hUCMS cells. The graft cells were recovered at 2 days and 1 week, but not at 6, 10 or 12 weeks post-transplantation. Quantitative assessment of host TH-positive midbrain dopaminergic neurons revealed a positive correlation between the behavioral improvement and TH-positive cell number in the low-density (1000 cells) transplant group, showing that the hUCMS cells may play a role in rescuing damaged host dopaminergic neurons and promote improvement of motor deficits in PD-model rats. In summary, hUCMS cells appear to be mesenchymal stem cells that can be harvested in great numbers from a non-controversial, inexhaustible source. Human UCMS cells show therapeutic benefit in PD model rats, but the mechanism by which they promote improvement is presently unknown.
Keywords: Parkinson's disease; Stem cells; Transplantation; Umbilical cord; Biology, Neuroscience (0317)